Evaluation of Efficiency of Active Clamp Dual Flyback Inverter for Photovoltaic Systems using Simulation Method - Šul, R.; Dobrucký, B.; Čerňan, P. (Elektronika ir Elektrotechnika, 2010)
Dual flyback inverter (DFBI) is one of the preferred topologies for isolated low cost low power photovoltaic (PV) applications. It converts PV cells DC voltage to output AC voltage using single power stage. It is important to understand loss distribution of DFBI be able to reach efficiency limits of this topology. This paper evaluates the efficiency of DFBI based on computer simulation results worked-out by Simetrix circuit simulator. Ill. 7, bibl. 10 (in English; summaries in English, Russian and Lithuanian).